2011
DOI: 10.3109/07435800.2010.514877
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Thyroid Function and Bone Mineral Density in Euthyroid Healthy Subjects in Taiwan

Abstract: Our study did not find significant correlations between TSH and BMD in both men and women with normal thyroid function in Taiwan. Weak negative correlations existed between T4 and BMD in postmenopausal women and young men. Further studies with measurement of FT4 and TSH and with a longitudinal design may shed light on this population difference.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 15 publications
1
21
1
1
Order By: Relevance
“…Similar to the current study, Murphy et al also reported an inverse correlation between fT 4 and BMD by multiple linear regression. Other studies have also demonstrated that women with higher fT 4 levels within the normal reference range have lower BMD, but they found little or no association between BMD and TSH (10,11,12,25). Interestingly, in a study from Taiwan using a similar cross-sectional design in women of comparable age to the current study, no relation was demonstrated between TSH and BMD, while the authors found a significant but weak correlation between BMD and fT 4 in postmenopausal women (11).…”
Section: European Journal Of Endocrinologymentioning
confidence: 45%
See 2 more Smart Citations
“…Similar to the current study, Murphy et al also reported an inverse correlation between fT 4 and BMD by multiple linear regression. Other studies have also demonstrated that women with higher fT 4 levels within the normal reference range have lower BMD, but they found little or no association between BMD and TSH (10,11,12,25). Interestingly, in a study from Taiwan using a similar cross-sectional design in women of comparable age to the current study, no relation was demonstrated between TSH and BMD, while the authors found a significant but weak correlation between BMD and fT 4 in postmenopausal women (11).…”
Section: European Journal Of Endocrinologymentioning
confidence: 45%
“…Other studies have also demonstrated that women with higher fT 4 levels within the normal reference range have lower BMD, but they found little or no association between BMD and TSH (10,11,12,25). Interestingly, in a study from Taiwan using a similar cross-sectional design in women of comparable age to the current study, no relation was demonstrated between TSH and BMD, while the authors found a significant but weak correlation between BMD and fT 4 in postmenopausal women (11). However, because of the inverse relationship between TSH and T 4 that results from negative feedback regulation of the HPT axis (as reviewed elsewhere (5, 10)), it is not possible to make a distinction between the physiological importance of higher fT 4 levels compared with lower TSH levels.…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%
See 1 more Smart Citation
“…In the Rotterdam study of 1151 euthyroid men and women aged over 55 years, femoral neck BMD correlated positively with TSH and negatively with fT 4 (van der Deure et al 2008). A recent large Taiwanese study of 2957 euthyroid healthy male and female individuals over 45 years of age again reported a negative correlation between BMD and fT 4 but found no correlation with TSH (Lin et al 2011). A cross-sectional study of 677 healthy young men studied at the time of peak bone mass (25-45 years) reported that higher concentrations of fT 3 and Murphy et al 2010).…”
Section: Skeletal Effects Of Thyroid Hormone Concentrations In the Upmentioning
confidence: 99%
“…A normal or high normal TSH level is known to preserve the BMD [9]. Hormone replacement therapy and calcium supplementation are presently available as the therapeutic modalities for the postmenopausal complications [10]. In addition to this, an early detection and correction of the abnormal TSH levels could help in the prevention of these complications which are observed in PMW [4,8].…”
Section: Introductionmentioning
confidence: 99%